4(x-2)=9x-23

Simple and best practice solution for 4(x-2)=9x-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-2)=9x-23 equation:



4(x-2)=9x-23
We move all terms to the left:
4(x-2)-(9x-23)=0
We multiply parentheses
4x-(9x-23)-8=0
We get rid of parentheses
4x-9x+23-8=0
We add all the numbers together, and all the variables
-5x+15=0
We move all terms containing x to the left, all other terms to the right
-5x=-15
x=-15/-5
x=+3

See similar equations:

| 6.4÷8=y | | 15x+4=8x+4 | | 11u-10u=13 | | 5p+p=20 | | 20d+19d=14 | | 14’6=-16^2+s | | 4/3w-2/3w=-12 | | 2x-18=9-x | | -2x-5=-6x-37 | | 19i−5=128 | | 53=-3-8n | | (800)2+(600)2=10000x | | (800)2+(600)=10000x | | 2q-5=3q-3= | | 10000=(800x)2+(600x)2 | | 8t-24=2t-6= | | (7x+6)/7+8(8x-2)=(7x-6)/7 | | 7z-1=8z-4= | | 4(5+3)=2(9x+3) | | 7x+677x+67+8(8xx-2)=7x−677x−67. | | 6t-3=7t-8= | | 2c-2=4c-6=0.4 | | –3/4m=21 | | 10=5+6x | | 30=5+6x | | 45=5+6x | | 40=5+6x | | 0.10x+0.03(38500-x)=2590 | | 50=5+6x | | 100=5+6x | | –130=g–19 | | 5x-3=7+5 |

Equations solver categories